Impact of baseline serum IL‐8 on metastatic hormone‐sensitive prostate cancer outcomes in the Phase 3 CHAARTED trial (E3805). Issue 16 (19th September 2020) - Harshman, Lauren C.; Wang, Victoria X.; Hamid, Anis A.; Santone, Gabriella; Drake, Charles G.; Carducci, Michael A.; DiPaola, Robert S.; Fichorova, Raina N.; Sweeney, Christopher J.
Abstract: Background: The immunosuppressive cytokine interleukin‐ 8 (IL‐8), produced by tumor cells and some myeloid cells, promotes inflammation, angiogenesis, and metastasis. In our discovery work, elevated serum IL‐8 at androgen deprivation therapy (ADT) initiation portended worse overall survival (OS). Leveraging serum samples from the phase 3 CHAARTED trial of patients treated with ADT +/− docetaxel for metastatic hormone‐sensitive prostate cancer (mHSPC), we validated these findings. Methods: Two hundred and thirty‐three patients had serum samples drawn within 28 days of ADT initiation. The samples were assayed using the same Mesoscale Multiplex ELISA platform employed in the discovery cohort. After adjusting for performance status, disease volume, and de novo/metachronous metastases, multivariable Cox proportional hazards models assessed associations between IL‐8 as continuous and binary variables on OS and time to castration‐resistant prostate cancer (CRPC). The median IL‐8 level (9.3 pg/ml) was the a priori binary cutpoint. Fixed‐effects meta‐analyses of the discovery and validation sets were performed. Results: Higher IL‐8 levels were prognostic for shorter OS (continuous: hazard ratio [HR] 2.2, 95% confidence interval [CI]: 1.4–3.6, p = .001; binary >9.3: HR 1.7, 95% CI: 1.2–2.4, p = .007) and time to CRPC (continuous: HR 2.3, 95% CI: 1.6–3.3, p < .001; binary: HR 1.8, 95% CI: 1.3–2.5, p < .001) and independent of docetaxel use, disease burden, and time of metastases. Meta‐analysis including the discovery cohort, also showed that binary IL‐8 levels >9.3 pg/ml from patients treated with ADT alone was prognostic for poorer OS (HR 1.8, 95% CI: 1.2–2.7, p = .007) and shorter time to CRPC (HR 1.4, 95% CI: 0.99–1.9, p = .057). Conclusions: In the phase 3 CHAARTED study of men with mHSPC at ADT initiation, elevated IL‐8 portended worse survival and shorter time to castration‐resistant prostate cancer independent of docetaxel administration, metastatic burden, and metachronous versus de novo metastatic presentation. These findings support targeting IL‐8 as a strategy to improve mHSPC outcomes.